Hubungan Penempatan Kerja dengan Kinerja Sumber Daya Manusia Kesehatan di Rumah Sakit Pinna Bekasi Tahun 2025 - Muhammad Hafiizh; Ria Efkelin; Sarah Geltri Harahap (Universitas Muhammadiyah Manado, 2025)
Job placement in accordance with the competence of health workers is a key factor in improving the quality of hospital services. However, there is still a mismatch in placement that has an impact on the low quality of service. This study aims to analyze the relationship between job placement, which includes education, knowledge, skills, and work experience, with the performance of health human resources (HRH) at Pinna Hospital Bekasi. The study used a quantitative approach with a cross-sectional design. The research sample was taken by total sampling method, involving 100 respondents from various health worker professions. Data were collected through questionnaires and analyzed with the Spearman correlation test. Univariate results showed 97% of SDMK had been placed according to their field of expertise, while the performance of SDMK reached 100%. Spearman test showed significant relationships between: education and performance (p-value <0.001; r=0.377), job knowledge and performance (p-value <0.001; r=0.469), job skills and performance (p-value <0.001; r=0.593), work experience and performance (p-value <0.001; r=0.489), and job placement and performance (p-value <0.001; r=0.574). It can be concluded that job placement in accordance with the competence of health workers plays an important role in improving the performance of HRK at Pinna Bekasi Hospital. Hospitals are advised to maintain the existing placement system and provide ongoing training to improve performance